DEVELOPMENT OF A QUALITY MANAGEMENT SYSTEM FOR PRECAST CONCRETE FACTORIES - Seo, Wonseok; Choi, Byungjoo; Shin, Dongyoun; Kim, Jinyoung (Journal of Civil Engineering and Management, 2023)
The precast concrete (PC) method involves manufacturing reinforced concrete building components in a factory that are then transported to and assembled on a construction site. Compared to conventional methods, PC is widely employed as an advantageous means of creating a sustainable environment and improving construction quality. However, due to time and cost increase, many modern PC factories inspect only randomly selected component samples, for which they write inspection reports using paper-based forms. The storage and management of these documents associated with inspections within factories are essential because any defects that occur during the manufacturing process adversely affect the subsequent delivery and assembly activities. In this study, a mobile application capable of automated documentation and the storage, and input of systematic data was developed to generate a system for comprehensive quality management and assurance within PC factories. The developed system was tested in a PC factory, achieving a 47% time-saving rate compared to the conventional inspection method. Inspection reports of the developed system contain considerably more information than those of the conventional method and fundamentally prevent the risk of document damage and loss as they are automatically archived on a server in digital format.
Keywords: Concrete method; Construction sites; Conventional methods; Inspection report; Off-site construction; OSC; Quality inspection; Quality management systems; Reinforced concrete buildings; Sustainable environment; automation; inspection report; off-site construction; OSC; precast concrete; quality inspection